A Microenvironment Dual‐Responsive Nano‐Drug Equipped with PD‐L1 Blocking Peptide Triggers Immunogenic Pyroptosis for Prostate Cancer Self‐Synergistic Immunotherapy. (25th January 2023) - Wang, He; Gao, Zhiyuan; Jiao, Di; Zhang, Yufan; Zhang, Jingtian; Wang, Tianjiao; Huang, Yuhua; Zheng, Donghui; Hou, Jianquan; Ding, Dan; Zhang, Weijie
Abstract: Induction of immunogenic cell death (ICD) in tumor combined with immune checkpoint blockade (ICB) therapy is widely developed to improve the efficacy of cancer immunotherapy. However, the current ICD induced based on apoptosis, i.e., immunogenic apoptosis, is often restricted in immunogenicity owing to the inflammatory quenching that occurs early in apoptosis. Recently, pyroptosis is demonstrated to be a more efficient ICD form, i.e., immunogenic pyroptosis. The cell contents released during pyroptosis can powerfully activate tumor immunogenicity. Herein, first, it is demonstrated that lower doses of epigenetic drug decitabine can increase GSDME expression in prostate cancer (PCa) RM‐1 cells and successfully induce an apoptosis‐pyroptosis transition after photodynamic therapy (PDT). Subsequently, a microenvironment dual‐responsive nano‐drug equipped with PD‐L1 blocking peptide (TSD@LSN‐D) is developed for self‐synergistic cancer immunotherapy. The poorly immunogenic RM‐1 PCa model confirm that the powerful antitumor immune response evoked by TSD@LSN‐D not only can effectively inhibit the primary tumor but also form a long‐term immune memory to prevent PCa recurrence and metastasis. To the best of authors' knowledge, this work presents the first concept that promotes the apoptosis–pyroptosis transition after tumor PDT through epigenetic modulation. Furthermore, the powerful combination of immunogenic pyroptosis with ICB opens a new platform for PCa immunotherapy. Abstract : In this work, a microenvironmentally dual‐responsive nano‐drug, TSD@LSN‐D, for prostate cancer self‐synergistic immunotherapy is developed. Within tumor cells, decitabine assists the occurrence of immunogenic pyroptosis after PDT. The powerful immunomodulatory effects triggered by TSD@LSN‐D not only stimulate a solid anti‐tumor immune response to suppress the primary tumor, but also create a long‐term immune memory to prevent tumor recurrence and metastasis.